Pengaruh Penggunaan Media Audiovisual Berbasis Digital Terhadap Keterampilan Literasi Membaca Permulaan Di Kelas 2 Min 6 Aceh Utara - Suci Aulia Safira; Nisa Mawaddah; Syibbra Malasi; Selvi Saprina; Samsul Bahri (Indonesian Journal of Teaching and Teacher Education, 2025)
This study aims to examine the effect of using digital audiovisual media on the literacy skills and early reading abilities of second-grade students at MIN 6 Aceh Utara. This study uses a quantitative approach with a pre-experimental design involving one experimental class. The research instrument is an oral test administered in the form of a pre-test and post-test. The total sampling for this study was 10 second-grade students at MIN 6 Aceh Utara. Data analysis in this study used a parametric test, namely a dependent difference test (t-test). The results showed a significant effect from the dependent t-test results, namely 7.927, which was greater than 1.883 in the students' early reading skills. The average pre-test score was 57, which is categorized as very low. After being given treatment with digital audiovisual media, the average post-test score increased to 89.5, which is categorized as very high. This increase proves that the use of audiovisual media can effectively improve students' early reading literacy skills.